EARLY MODES OF TRANSPORT IN THE UNITED STATES (Промышленный Транспорт Казахстан, 2025)
The belief that modern alternative vehicles and modes of transport continue to failprimarily for technical reasons glosses over the importance of the economic, political, social andcultural dimensions of gasoline powered automobiles. This article investigates the changes that caused manufacturers and customers to abandon bicycles, horses, electric vehicles, cable cars,trolleys, and trains and to overwhelmingly prefer gasoline-powered vehicles from 1890 to 1940in the United States. It then focuses on the lessons that the historical transition to gasolinevehicles offers modern policymakers.